Genetic Basis of Azole and Echinocandin Resistance in Clinical Candida glabrata in Japan - Khalifa, Hazim O. (Antimicrob Agents Chemother, 2020)
Infections caused by Candida glabrata have caused worldwide concern, especially when they are associated with increasing echinocandin and azole resistance. In this study, we analyzed the molecular mechanisms of azole and echinocandin resistance in C. glabrata isolates obtained from hospitalized patients in Japan from 1997 to 2019. All isolates were checked phenotypically for resistance and genotypically for mutations in PDR1, ERG11, hot spot 1 (HS1), HS2, and HS3 of FKS1, and HS1 and HS2 of FKS2, and all isolates were genotyped by multilocus sequence typing (MLST). Interestingly, 32.6% of the isolates were resistant to caspofungin, and 4.7% were resistant to micafungin. The isolates showed low rates of resistance to azoles, ranging from 2.3% to 9.3%, and only 4.7% of the isolates were non-wild type for flucytosine susceptibility. For the first time in Japan, 4.7% of the isolates were identified as multidrug-resistant strains. Nonsynonymous mutations in PDR1, including two novel mutations associated with azole resistance, were identified in 39.5% of the isolates, and a single nonsynonymous mutation was identified in ERG11. Nine isolates from the same patient harbored nonsynonymous mutations in HS1 of FKS2, and a single isolate harbored a single nonsynonymous mutation in HS1 of FKS1. MLST genotyping revealed 13 different sequence types (STs), with 3 new STs, and ST7 was the most prevalent among the patients (35%) and was associated with high resistance rates. Our results are of crucial clinical concern, since understanding the molecular mechanisms underlying fungal resistance is imperative for guiding specific therapy for efficient patient treatment and promoting strategies to prevent epidemic spread.